Evaluacion del crecimiento en diámetro y altura de la especie Swietenia macrophylla “Caoba” a diferentes dosis de fertilización en las plantaciones del CIEFOR puerto Almendra, Loreto, Perú – 2022 - Sandoval Arimuya, Bruce Brando Boris (2024)
Fertilizers are characterized by being organic and inorganic, which provide essential nutrients for plants, improving their health, resistance and ability to produce quality fruits, flowers and leaves. Likewise, their appropriate choice depends on the type of plant, soil and specific objective. The objective of this research work was to evaluate the growth in diameter and height of Swietenia macrophylla, under different types of fertilization: NPK, phosphate rock and Bayfolán liquid foliar fertilizer. The present study was carried out at the Forestry Research and Teaching Center (CIEFOR) of the Faculty of Forestry Sciences of UNAP, under a randomized complete block experimental design, with four treatments: Control (t0), NPK 100 g (t2), phosphate rock 100 g (t3) and Bayfolán foliar fertilizer 100 ml (t4). The results determined that the treatment with Bayfolan foliar fertilizer promoted the highest average growth in height (84.81 cm), while the treatment with NPK recorded the highest average growth in diameter (16.57 mm) and the highest survival rate (34 plants 85%). The study concluded that no significant differences were found in height growth and survival between treatments. However, growth in diameter was significantly greater with NPK treatment.